Phase II studies to select the formulation of a multivalent HPV L1 virus-like particle (VLP) vaccine - Luxembourg, Alain; Brown, Darron; Bouchard, Celine; Giuliano, Anna R; Iversen, Ole-Erik; Joura, Elmar A; Penny, Mary E; Restrepo, Jaime A; Romaguera, Josefina; Maansson, Roger; Moeller, Erin; Ritter, Michael; et al. (Human vaccines & immunotherapeutics, 2015)
Our objective was to develop a multivalent prophylactic HPV vaccine that protects against infection and disease caused by HPV16/18 (oncogenic types in existing prophylactic vaccines) plus additional oncogenic types by conducting 3 Phase II studies comparing the immunogenicity (i.e., anti-HPV6/11/16/18 geometric mean titers [GMT]) and safety of 7 vaccine candidates with the licensed quadrivalent HPV6/11/16/18 vaccine (qHPV vaccine) in young women ages 16-26. In the first study (Study 1), subjects received one of 3 dose formulations of an 8-valent HPV6/11/16/18/31/45/52/58 vaccine or qHPV vaccine (control). In Study 2, subjects received one of 3 dose formulations (termed low-, mid-, and high-dose formulations, respectively) of a 9-valent HPV6/11/16/18/31/33/45/52/58 vaccine (9vHPV vaccine) or qHPV vaccine (control). In Study 3, subjects concomitantly received qHPV vaccine plus 5-valent HPV31/33/45/52/58 or qHPV vaccine plus placebo (control). All vaccines were administered at day 1/month 2/month 6. In studies 1 and 3, anti-HPV6/11/16/18 GMTs at month 7 were non-inferior in the experimental arms compared with the control arm; however, there was a trend for lower antibody responses for all 4 HPV types. In Study 2, this immune interference was overcome with the mid- and high-dose formulations of the 9vHPV vaccine by increasing antigen and adjuvant doses. In all 3 studies, all vaccine candidates were strongly immunogenic with respect to HPV31/33/45/52/58 and were well tolerated. Based on the totality of the results, the middle dose formulation of the 9vHPV vaccine was selected for Phase III evaluation. Each 0.5mL dose contains 30μg/40μg/60μg/40μg/20μg/20μg/20μg/20μg/20μg of HPV6/11/16/18/31/33/45/52/58 virus-like particles, and 500μg of amorphous aluminum hydroxyphosphate sulfate adjuvant.ClinicalTrials.gov numbers NCT00260039, NCT00543543, and NCT00551187.